2020
DOI: 10.1103/physrevmaterials.4.045402
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study on material properties and stability of inorganic halide perovskite solid solutions CsPb(I1xBrx)3

Abstract: All-inorganic halide perovskites have attracted a great interest as a promising light harvester of perovskite solar cells due to their enhanced chemical stability. In this work we investigate the material properties of solid solutions CsPb(I 1−x Br x ) 3 in cubic phase by applying the virtual crystal approximation approach within a density functional theory framework. First we check the validity of constructed pseudopotentials of the virtual atoms (X = I 1−x Br x ) by verifying that the lattice constants follo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…In this function, the bowing parameter reflecting the qualitative miscibility between the components of solid solution was found to be 0.52 eV, which is slightly higher than the experimental value of 0.47 eV for CsPb(I 1− x Br x ) 3 . 39 When compared with the organic–inorganic hybrid solid solutions, this value is smaller than 0.87 eV for MAPb(I 1− x Cl x ) 3 (ref. 43 ) but larger than 0.18 eV for MAPb(I 1− x Br x ) 3 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this function, the bowing parameter reflecting the qualitative miscibility between the components of solid solution was found to be 0.52 eV, which is slightly higher than the experimental value of 0.47 eV for CsPb(I 1− x Br x ) 3 . 39 When compared with the organic–inorganic hybrid solid solutions, this value is smaller than 0.87 eV for MAPb(I 1− x Cl x ) 3 (ref. 43 ) but larger than 0.18 eV for MAPb(I 1− x Br x ) 3 .…”
Section: Resultsmentioning
confidence: 94%
“…There are several first-principles studies on halide perovskite solid solutions, including all-inorganic compounds 37–41 and organic–inorganic hybrid ones, 42,43 using the supercell method and the efficient virtual crystal approximation (VCA) approach 44 within a density functional theory (DFT) framework. In particular, Zhou et al 37 and Ghaithan et al 38 reported the structural, electronic and optical properties of mixed halide perovskites CsPb(Br 1− x Cl x ) 3 using the supercell modeling.…”
Section: Introductionmentioning
confidence: 99%
“…When mixing Ge/Sn with Mg, the band gap is found to increase with the Mg content x following the quadratic function of E g ( x ) = E g (0) + [ E g (1) − E g (0) − b ] x + bx 2 with the bowing parameter b (ref. 40 and 44 ) (see Table S7 and Fig. S4 † ).…”
Section: Resultsmentioning
confidence: 99%
“… 39–41 The cesium lead halide perovskites CsPbX 3 (X = Br, I) are promising photocatalysts for H 2 production in the form of quantum dots (QDs) with a good structural stability under the reaction conditions. 42,43 When mixing iodide and bromide to form CsPbBr 3− x I x with a band gap funnel structure, 44,45 the CsPbBr 3− x I x /Pt photocatalyst has a high stability with HER capability in a saturated HBr/HI mixed solution. 45 To avoid the toxicity problem from lead, 46 remarkable research endeavors were devoted to developing lead-free halide perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded. The Supporting Information contains additional figures, powder X-ray diffraction patterns, IR spectra calculations [ 33 , 51 , 52 ], calculated band structure [ 53 , 54 , 55 , 56 , 57 ], elemental composition data, crystal morphology, bond length and bond angle data. Figures S1–S6: Asymmetric unit of 1 – 5 .…”
mentioning
confidence: 99%